Analisis Harga Saham Menggunakan Metode Value Investing - Ayu Yuliana; Jawoto Nusantoro; Gustin Padwa Sari (Universitas Muhammadiyah Metro, 2026)
This study analyzes the stock prices of the primary consumer goods industry sector on the Indonesia Stock Exchange for the 2021-2024 period to identify undervalued stocks and recommend investment decisions. Using the value investing ratio analysis method, this study shows that INDF shares are undervalued with a margin of safety of 47.55% and are suitable for purchase because the share price is below intrinsic value. Financial ratios show INDF meets Graham Screener criteria with stables EPS, reasonable PER, high BVPS, low PBV and controlled DER. Meanwhile, ICBP, CPIN and MYOR stocks are classified as overvalued and need futher consideration before buying, it is advisable to sell as there is a possibility that the share price will decline.